Assessing serum albumin concentration following exercise‐induced fluid shifts in the context of the athlete biological passport. Issue 6 (20th February 2019) - Miller, Geoffrey D.; Teramoto, Masaru; Smeal, Stacy J.; Cushman, Dan; Eichner, Daniel
Abstract: Purpose: The hydration status of an athlete at the time of a doping control sample collection is an important factor to consider when reviewing athlete biological passports (ABPs). Dehydration results in a reduction of the circulating plasma volume (PV), which may lead to artificially high values of some blood parameters. This study aimed to identify whether serum albumin could serve as a single marker of fluid shifts, which are not currently accounted for in the hematological passport. An additional marker could be used to assist experts when interpreting irregularities in the ABP. Methods: Twelve subjects underwent multiple controlled exercise trials designed to induce varying levels of PV shifts. Pre‐exercise blood samples were collected to establish baseline values for individual passports. During exercise interventions, blood samples were collected before the start of exercise and at 10 minute, 1 hour, 2 hours, and 24 hours following exercise. Results: Significant increases in hematological parameters – hemoglobin [Hb], hematocrit (HCT), albumin (ALB), and calculated OFF‐score – were identified at varying time points following fluid shift‐inducing exercise. Changes in ALB correlated strongly with changes in [Hb] ( r = 0.753 ) and with estimated PV shifts ( r = −0.764 ). In analyzing ABPs, the resulting increases in Hb did not trigger any atypical findings at 99% specificity. Perspective: Monitoring changes in ALB longitudinally may assist experts when reviewing PV shifts in the biological passport. Abstract : Athletes were subjected to numerous exercise interventions designed to induce varying levels of plasma volume shifts. Serum albumin concentration was longitudinally measured in these athletes before and after exercise, and the resulting values were compared to hematological parameters from the athlete biological passport.